Analisis Hasil Belajar Matematika Siswa Pada Materi Pecahan Kelas VII Terhadap Pengaruh Pembelajaran Problem Posing (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
Education that is able to support development in the future is education that is able to develop the potential of students, so that those concerned are able to face and solve the problems of life they face. Education must touch the potential of conscience and potential competence of students. The concept of education is increasingly important when someone has to enter life in society and the world of work, because the person concerned must be able to apply what is learned at school to deal with problems faced in daily life now and in the future (Suhendri & Mardalena, 2015).